Effect of Metal Ions on the Interaction of Condensed Tannins with Protein - Liangliang Zhang; Qinhao Guan; He Zhang; Lihua Tang (Foods, 2023)
A quantitative analysis of the precipitate effects of metal ions (Al3+, Fe2+, Cu2+, Zn2+) by bovine serum albumin (BSA) on two condensed tannins (CT) from sorghum and plum was presented in this study. The results showed that adding metal ions enhanced the precipitation of proteins by CT, depending on the type and concentration of the metal ions used in the reaction system. The presence of metal ions and precipitation results on the CT–protein complex showed that Al3+ and Fe2+ had a higher binding ability with CT and a weaker influence on the precipitation of the CT–protein complex than Cu2+ and Zn2+. However, when the initial reaction solution contained excessive amounts of BSA, the extra addition of metal ions had no significant effect on the amount of BSA precipitation. Reversely, adding Cu2+ or Zn2+ into the reaction solution increased the amount of precipitated BSA when the amount of CT was excessive. In addition, the amounts of CT from plum, rather than sorghum, generated more protein precipitate in the presence of Cu2+ or Zn2+, which may be due to the different binding modes between the metal ion and the CT–BSA complex. This study also proposed a model of the interaction between the metal ion and the CT–protein precipitate.